2019
DOI: 10.1101/639617
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Myeloid Lineage Enhancers Drive Oncogene Synergy in CEBPA/CSF3R Mutant Acute Myeloid Leukemia

Abstract: Acute Myeloid Leukemia (AML) develops due to the acquisition of mutations from multiple functional classes. Here, we demonstrate that activating mutations in the granulocyte colony stimulating factor receptor (CSF3R), cooperate with loss of function mutations in the transcription factor CEBPA to promote acute leukemia development. This finding of mutation-synergy is broadly applicable other mutations that activate the JAK/STAT pathway or disrupt CEBPA function (i.e. activating mutations in JAK3 and Core Bindin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 47 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…We previously reported that retroviral expression of mutant CSF3R (CSF3R T618I ) and C-terminal mutant CEBPA (CEBPA V314VW ) in mouse bone marrow is sufficient to permit indefinite culture in cytokine-free media (17). To identify therapies active against this subtype of AML, we performed a functional screen utilizing a library of compounds for which we have accumulated sensitivity data on a large number of primary patient samples ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously reported that retroviral expression of mutant CSF3R (CSF3R T618I ) and C-terminal mutant CEBPA (CEBPA V314VW ) in mouse bone marrow is sufficient to permit indefinite culture in cytokine-free media (17). To identify therapies active against this subtype of AML, we performed a functional screen utilizing a library of compounds for which we have accumulated sensitivity data on a large number of primary patient samples ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During normal blood development, LSD1 is present in numerous chromatin-remodeling complexes that decommission enhancers, leading to gene silencing (19). As mutant CEBPA produces a unique epigenetic landscape in AML and enhancer activation is crucial to the oncogenic activity of CEBPA mutant AML (17,20), we investigated the efficacy of multiple targeted epigenetic inhibitors against our CEBPA/ CSF3R mutant cell line. We assessed the in vitro cytotoxicity of inhibitors of LSD1 (GSK2979552 and GSK-LSD1), Jumonji histone demethylase (KDM4C, JHDM inhibitor VIII), disruptor of telomeric silencing 1-like (DOT1L, EPZ004777), enhancer of zeste 2 (EZH2, UNC1999), histone deacetylases (HDAC, panobinostat), and DNA methyl transferases (DNMT, azacitidine) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations